Integrating Solar PV, Battery Storage, and Demand Response for Industrial Peak Shaving: A Systematic Review on Strategy, Challenges and Case Study in Malaysian Food Manufacturing - Zahari N.E.M.; Mokhlis H.; Mubarak H.; Mansor N.N.; Sulaima M.F.; Ramasamy A.K.; Zulkapli M.F.; Ja'apar M.A.B.; Jaafar M.; Marsadek M.B. (Institute of Electrical and Electronics Engineers Inc., 2025)
As global energy demands surge, the industrial sector, a key player, is undergoing a crucial transition towards sustainable practices while ensuring efficient production. The implementation of electricity peak shaving, a strategy that minimizes consumption during peak demand periods, emerges as a promising solution. This proactive approach delivers both environmental and economic benefits, such as reduced greenhouse gas emissions and lower energy costs. Recent advancements in the integration of solar photovoltaics, battery storage, and demand response programs have made peak shaving even more attractive. This integrated approach, has garnered significant attention due to its potential to optimize energy use without disrupting industrial operations, offers a path towards responsible industrial sustainability. However, widespread adoption of peak shaving in both industrial settings and across Malaysia is facing early adoption challenges. To bridge this gap, this paper presents a comprehensive systematic literature review, that examines the current state-of-the-art and strategies for peak shaving in the industrial sector. This review focuses on identifying key themes, including objectives, employed technologies, and implementation techniques. In addition, a case study on a Malaysian food manufacturing building is presented to demonstrate the versatility of hybrid solar PV and BESS systems. These systems can directly power operations, store solar energy in batteries, feed excess energy into the grid, and seamlessly switch to grid-supplied power when needed. The results of this case study showed a significant 6.9% reduction in energy costs and an 8.6% decrease in CO2 emissions. Leveraging insights from both literature and real-world projects, this study introduces the Industrial Peak Shaving framework to guide future research and implementation. The goal of this framework is to pave the way for broader and more socially and environmentally responsible industrial sustainability. ? 2024 The Authors.